Online Geoboard Media Improves Understanding of Two-dimensional Flat Shape Concepts in Elementary School Students - Sabil, Husni; Asrial, Asrial; Syahrial, Syahrial; Robiansah, Muhammad Andika; Zulkhi, Muhammad Dewa; Damayanti, Latipia; Kiska, Nurul; Silvia, Ninda; Ubaidillah, Ubaidillah (Universitas Pendidikan Ganesha, 2021)
In learning mathematics, 78.5% of students do not understand the material concepts taught by the teacher on geometry material. It is because the media used by the teacher in learning mathematics is not appropriate. Inappropriate media will make it difficult for students to understand the learning material, so that it has an impact on low student learning outcomes. This study aims to analyze the effect of using Geoboard online in improving students' understanding of mathematical concepts in the fourth-grade elementary school's Bangun Datar learning. This type of research uses the Mix method, namely data collection using qualitative and quantitative. Sampling using purposive sampling with a total of 28 students. The research design uses Explanatory Sequential Design. This study involves several variables as research categories, namely Student responses and Concept Understanding. Data analysis used descriptive and inferential statistics. The study results are that the variable of response and Concept Understanding has a significant influence, with a value of sig <0.05, and on each dominant variable in the excellent category, so that online geoboard media affects students' understanding of the flat wake concept. Therefore, Geoboard online media can be used as an alternative learning that is fun and suiTablefor children in elementary school. The implication of this research is to use learning media in helping students understand technology-based concepts.